Selection of local antiseptic for treatment and prevention of wound infection - A. V. Rodin (Амбулаторная хирургия, 2019)
The advantages and disadvantages of modern antiseptics for local treatment and prevention of wound infections are considered. On the basis of data of comparative clinical studies the advantages of topical drugs based on octenidine dihydrochloride in combination with phenoxyethanol are presented. The advantages of octenidine dihydrochloride/ phenoxyethanol as a local antiseptic for treatment and prevention of wound infections in case of wound defects, burns are described.